Modern Theories of Wisdom: Literature Review - Kondratieva, Veronika; Zarubin, Illia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article presents a theoretical analysis of modern theories of wisdom, considers the formation and essence of the concept of wisdom in psychology. At the end of the twentieth century, the interest of psychologists in the subject of wisdom began to grow. Wisdom as a concept is integral to any society, culture and time, it reveals those qualities of personality that help a person to be realized. The concept of wisdom requires theoretical justification and empirical research. In general, there are two main concepts of wisdom: one affirms the affective qualities more or less with the cognitive, inherent in man; the other focuses precisely on cognitive and reflexive abilities, ignoring emotional life. This typification has proved itself in several planes. In the history of philosophy, the understanding of wisdom had both an affective and a cognitive character, represented by East and West. Empirical studies of implicit concepts of wisdom conducted in recent years indicate the variability of perception of wisdom. In the East, the concept of wisdom is less analytical and more psychological than in the West, which requires an understanding not only of the intellectual, but also of the sensual (emotions, intuition, etc.). Cross-cultural empirical studies confirm the general difference in the perception of wisdom in different cultures. The influence of age on the manifestations of wisdom in humans should be noted separately. Research has shown that age negatively affects the intellectual component of wisdom, but is neutral to procedural knowledge. On the one hand, with age a person acquires experience that can interpret and extract new procedural knowledge from him. On the other hand, the fact that a person has life experience does not determine a person’s qualitative interpretation of what happened to him. The age factor cannot be decisive in becoming wise.
Keywords: wisdom; theories of wisdom; cognition